Fiscal developments and financial stress: a threshold VAR analysis - António Afonso; Jaromír Baxa; Michal Slavík (European Central Bank (ECB), 2011)
We use a threshold VAR analysis to study whether the effects of fiscal policy on economic activity differ depending on financial market conditions. In particular, we investigate the possibility of a non-linear propagation of fiscal developments according to different financial market stress regimes. More specifically we employ a quarterly dataset, for the U.S., the U.K., Germany and Italy, for the period 1980:4-2009:4, encompassing macro, fiscal and financial variables. The results show that (i) the use of a nonlinear framework with regime switches is corroborated by nonlinearity tests; (ii) the responses of economic growth to a fiscal shock are mostly positive in both financial stress regimes; (iii) financial stress has a negative effect on output growth and worsens the fiscal position; (iv) the nonlinearity in the response of output growth to a fiscal shock is mainly associated with different behaviour across regimes; (v) the size of the fiscal multipliers is higher than average in the last crisis.
Keywords: E62; G15; H60; 330; financial markets; Fiscal Policy; threshold VAR